Palliative Medicine, an Urgent Public Health Need in the Developing World - Jagwe, Jack; Merriman, Anne (Journal of Public Health Policy, 2007)
‘‘Palliative Care: A Public Health Priority in Developing Countries’’ in this issue of the Journal demands the attention of all those addressing public health problems in the developing world. Since 2000, palliative care has been an essential clinical service, in the context of HIV/AIDS, in the health strategic plan of Uganda, but has any other country taken it up? Palliative care is coming under health policies for HIV/AIDS not cancer, because HIV underlies many of the top 10 causes of death in developing countries today. To most countries in the Developing world, palliative care is a new specialty. Dame Cicely Saunders, OBE, first researched and modernized hospice and palliative medicine, in 1967. In 1986, the World Health Organization (WHO) took an interest in the problem of relief from pain for persons facing life-threatening illnesses, addressing mainly cancer. In 1986, WHO published their best seller, ‘‘Cancer Pain Relief’’(1) and sent it to all Governments in the world.
Keywords: Palliative Care; Palliative Medicine; public health